Validation of radiological reduction criteria with intraoperative cone beam CT in unstable syndesmotic injuries - Vetter, Sven Y.; Euler, Jeannie Jessica; Beisemann, Nils; Swartman, Benedict; Keil, Holger; Grützner, Paul Alfred; Franke, Jochen (European journal of trauma and emergency surgery, 2021)
Acute unstable syndesmotic lesions are regularly treated with closed or open reduction and fixation with either a positioning screw or tight rope. Conventional fluoroscopy is limited to identify a malreduction of the ankle mortise. The aim of the study was to validate the reduction criteria of intraoperative cone beam CT in unstable syndesmotic injuries by analyzing the clinical outcome.
Published: 25 February 2020
Gesehen am 02.09.2021